INSTITUTIONAL COOPERATION IN THE DEVELOPMENT OF RAFTING TOURISM IN SEI BOLON, BULUH DURI VILLAGE, SIPISPIS DISTRICT - Searca Agung Nugroho; Femmy Indriani Dalimunthe; Bahagia Tondang (Asosiasi Dosen Muda Indonesia, 2022)
White water rafting is a sport that has a recreational aspect and has now become one of the mainstays of Indonesian tourism in the last 10 years. In the North Sumatra region, there are three locations that are featured rafting objects and one of them is white water rafting at Sei Bah Bolon which is located in Buluh Duri Village, Sipispis District, Serdang Bedagai (Sergai) Regency. White water rafting tourism in Sei Bah Bolon has tremendous potential that can still be explored and developed in the future, where until now, the development of white water rafting tourism has resulted from good cooperation between the relevant institutions and the institutions that are quite diverse from formal and informal institutions. With the collaboration between these institutions, which is considered the main factor in the development of rafting tourism in Sei Bah Bolon, this thesis uses a qualitative research method, where data is collected through many interactions carried out with various parties, both in institutions that are actively involves, as well as at the rafting tourist sites. From the many interactions, results are obtained that show how the success, shortcomings, hopes, and future potential of tourism development in Sei Bah Bolon are obtained. With the existence of other white water rafting attractions that are benchmarks in terms of rafting development, in which there is also a collectivity from institutions in its development, it is indeed concluded that collective cooperation is very important for the potential for tourism development in the Sei Bah rafting tourist attraction. Bolon, so that by paying attention to things that develop and to achieve sustainability, in the future it remains to be re-identified what institutions and how their duties and functions will be related to rafting in the future.